Cryptic ecology among host generalist Campylobacter jejuni in domestic animals. Issue 10 (25th April 2014) - Sheppard, Samuel K.; Cheng, Lu; Méric, Guillaume; de Haan, Caroline P. A.; Llarena, Ann‐Katrin; Marttinen, Pekka; Vidal, Ana; Ridley, Anne; Clifton‐Hadley, Felicity; Connor, Thomas R.; Strachan, Norval J. C.; Forbes, Ken; et al.
Abstract Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.